Implementation Of Artificial Intelligence In Crop Monitoring For Agriculture - Saragada, D V V S B Reddy; Swaroopa, Korla (Journal of Neonatal Surgery, 2025)
Farmers have stopped cultivation in present days due to not being able to get the facilities which would help them in the process. On top of this, animals are causing other issues that frustrate the farmers and drive them to abandon crop cultivation; You can get our paper immune to the latter. Paper aims to scare the animal involving our fields to destroy. Wildlife intervention often leads to destruction of locally owned crops. This creates protection of yield and to protect the yield, those organisms need to be terrified — which is the only way of saying that the farmer is a worry to those organisms.” Farmers cannot constraint the entire fields and guard it. Due to time and resource constraints, it is impractical for farmers to monitor and guard whole fields by hand. Thus, there is an urgent requirement for novel, automated systems that can effectively deter animal poaching in a safe manner. The use of such technologies allows farmers to protect crops, improve productivity, and minimize the need for real-time human intervention. This article describes an everyday application that can be used to prevent crop-damage on agriculture farms by animals. To address this problem, this research utilizes Global System for Mobile Communication (GSM) and Short Message Service (SMS) technology to present a useful, automatic system for the farmers. The proposed system approach depends on mobile telecommunication technology to send instant notification to inform farmers of a possible animal attack in their farms. This method gives instant responses by applying detection techniques along with GSM based alerts, which reduces the level of crop loss and yield security. The study endeavours to adapt the existing mobile communication infrastructure that is readily accessible, affordable, and conducive to a range of farmers in diverse locations, maximizing usability and cost efficiency. This Research paper it helps the concept of identification of a specific target by an image processing system and generating intolerable frequency than the targets audible range frequency.